PENGARUH KEPUASAN KERJA DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEINGINAN KELUAR KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI(STUDI KASUS DI CV. PUTRA TAMA JAYA) - Sartika, Dwi (Management Analysis Journal, 2014)
The  purpose  of  this  study  is  to  know  there  any  direct  and  indirect  relationship  between  job  satisfaction, organizational commitment and transformational leadership styles and relationship to turnover intention. The population is 294 people Blockboard production employees of CV Putra Tama Jaya and 170 samples obtained using  the  Slovin  formula.  Methods  of  data  collection  using  questionnaires,  methods  of  descriptive  analysis, multiple regression analysis and partial and path analysis using SPSS for Windows version 16. The results, there  is  a  direct  effect  of  job  satisfaction  on  employee  turnover  intention  (0.025<0.05),  job  satisfaction  on organizational  commitment  (0.007<0.05).  of  organizational  commitment  on  the  turnover  intention (0.023<0.05), transformational leadership style to organizational commitment (0.000<0.05), so that H1, H2, H3, and H4 is accepted, there is no direct relationship of transformational leadership style against the turnover intention (0.984> 0.05) H5 is not acceptable. Organizational commitment does not mediate the relationship between job satisfaction and the turnover intention against the wishes of transformational leadership style H6 and H7 out so not accepted.